Expanding English vocabulary using Google Lens: Insights from a real-time translation - Yusi Rahmawati; Haryani Haryani; Dwi Sulistyorini; Retno Indriyati (Universitas Aki, 2024)
This study explores the effectiveness of Google Lens in enhancing English vocabulary acquisition through its real-time translation capabilities. As technology increasingly integrates into educational practices, innovative tools like Google Lens offer potential benefits for language learners. This research assesses how real-time translation impacts vocabulary acquisition among English as a Second Language (ESL) learners. A mixed-methods approach was employed, involving quantitative analysis of vocabulary test scores before and after the intervention and qualitative analysis of learner experiences gathered through surveys and interviews. Participants included a diverse group of ESL students who used Google Lens to translate and learn new English words in various contexts over a specified period. The findings indicate that Google Lens significantly improves vocabulary retention and comprehension compared to traditional learning methods. Learners reported increased engagement and confidence in their language skills, attributing this to the immediate and contextual feedback provided by the tool. The study concludes that integrating Google Lens into language learning can be a powerful strategy to enhance vocabulary acquisition. This conclusion has practical implications for educators and learners, equipping them with the knowledge to effectively leverage technology in language education and improve their teaching and learning practices.